A metamorfose da natureza: implicações sociais, econômicas e socioambientais do turismo no Parque Nacional dos Lençóis Maranhenses - ROMEIRO, Ana Luiza Sousa (2023)
The creation of the Lençóis Maranhenses National Park by the State, in 1981, disregarded the previous occupation of this territory by traditional communities that historically manage and appropriate the elements of nature present in different environments of this integral protection conservation unit. Due to multiple interests at stake, this vast area has been the subject of disputes by different agents, who aim to explore its tourist potential. This framework enables the emergence of an arena of unequal dispute involving families from traditional communities that fight for the right to continue reproducing their way of life; entrepreneurs who aim to explore tourism in this region; tourists who seek to contemplate nature, and the State itself, which limits the traditional way of life of these families, and encourages tourism on a business basis. Taking this scenario as a reference, the analyzes carried out in the dissertation seek to understand the positive and negative social, economic and socio-environmental implications of tourism in the PNLM, taking as reference the movement of the agents involved. This dissertation is the result of research investments carried out in two locations in the Lençóis Maranhenses National Park (PNLM), in the municipality of Barreirinhas: Atins and Canto do Atins. Traditional communities that basically lived off fishing and shellfishing, but that after the reclassification of their territories into conservation units also started to develop, as a daily form of resistance, activities related to tourism according to the seasonality. Based on a qualitative methodology, it includes ethnographic information from consolidated field work through direct and participant observation, which allowed identifying the strategies used by families to remain in the territory.